#TITLE_ALTERNATIVE# - AUDIA ALFIAN (NIM 13702041), ROY
Steel Fiber Reinforced Castable Refractories (SFRCR) is a castable refractory which contain random short steel fiber as its reinforcement. Steel fiber is used to extend the product life cycle, increase the thermal shock resistance, and also to improve the mechanical properties of refractory. The unevenly distributed short fibers will produce non uniform mechanical properties. In order to improve that, a woven steel fiber were used to observe the mechanical properties behavior i.e. Modulus of Rupture (MOR) of the specimen. This research was carried out to study the effect of using continuous woven steel fiber reinforcement and its ply number variations to the MOR of LAMJ-1 refractory (Alumina Spinel Castable). The MOR properties were observed in several firing temperature from 105oC up to 1400oC, this was to observe the variations of the refractory in order to withstand external loading, including its own weight. The MOR tests were carried out at room temperature according to BS.1610. This test was chosen to analyze the transversal load that could be held by this refractory before it failed. To support the result, a micro structure analysis were undertaken by using Philips Scanning Electron Microscope XL-20 equipped with EDS DX-40 and then compositional phase analysis were carried out using an X-Ray diffraction. Between 105–816ºC, the fiber reinforcement addition of 1.8% was found doubled the MOR and increase up to three times after 3.6% fiber addition. Between 816ºC until 1150ºC the fiber addition decrease the MOR from 7.62 MPa at 816ºC to 3.85 MPa at 1150ºC with3.6% fiber addition. The MOR result also decreases after 1.8% fiber addition from 4.77 MPa at 816ºC to 2.57 MPa at 1150ºC. The decrease in MOR was thought to be contributed by the corroded steel fiber. The effect of temperature variations to the strength of refractory without any fiber addition was also observed. At 350ºC, the strength increases from 4.06 MPa to 4.74 MPa, which is comparable to the product strength at 105ºC. At 816ºC, the strength decreases from 4.74 MPa to 1.27 MPa. At 1150oC, the strength increases from 1.27 MPa to 3.85 MPa and is still increasing until 4.71 MPa at 1400ºC. urther research is required to study the strength decreasing mechanism between 05oC-350oC and also the behavior of this refractory on temperature above 1400oC using fiber that have a higher temperature corrosion resistance.